2022
DOI: 10.2196/37309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Text Messaging Intervention to Promote Preconception Micronutrient Supplement Use: Feasibility Study Nested in the Healthy Life Trajectories Initiative Study in South Africa

Abstract: Background Social messaging strategies such as SMS text messaging and radio are promising avenues for health promotion and behavior change in low- to middle-income settings. However, evidence of their acceptability, feasibility, and impact in the context of young women’s health and micronutrient deficiencies is lacking. Objective This study aimed to evaluate the feasibility of an automated 2-way text messaging intervention nested in an ongoing preconcep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The quantitative results of this study showed that a large proportion of individuals owned a mobile phone. This result is in line with previous literature, which has shown that mobile connectivity in South Africa has grown rapidly with a mobile penetration rate of >95%, with 91% of all phones being smartphones [1,17,24]. Although this was also corroborated by the qualitative findings, a key finding was that some participants were mobile phone sharers, whereas others had no phones at all and thus relied on their social networks who had phones and often depended on using these phones for a short while to be in touch with other individuals.…”
Section: Principal Findingssupporting
confidence: 93%
See 4 more Smart Citations
“…The quantitative results of this study showed that a large proportion of individuals owned a mobile phone. This result is in line with previous literature, which has shown that mobile connectivity in South Africa has grown rapidly with a mobile penetration rate of >95%, with 91% of all phones being smartphones [1,17,24]. Although this was also corroborated by the qualitative findings, a key finding was that some participants were mobile phone sharers, whereas others had no phones at all and thus relied on their social networks who had phones and often depended on using these phones for a short while to be in touch with other individuals.…”
Section: Principal Findingssupporting
confidence: 93%
“…These number changes were tracked from randomization to the trial. The number changes were categorized as (1) no number change, (2) 1 number change, or (3) >2 number changes.…”
Section: Quantitative Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations